All Deceptions Are Not Alike: Bayesian Mechanism Design with Social Norm Against Lying - Ville Korpela (Aboa Centre for Economics (ACE), 2014)
We say that a society has a weak norm against lying if, all other things being equal, agents rather lie in such a way that they do not get caught. We show that if this is the case, and it usually is, then Bayesian monotonicity is no longer a constraint in implementation and all incentive compatible social choice functions are Bayesian implementable. In contrast to the previous literature our result derives from a refinement of the standard Bayes-Nash equilibrium that does not rely on any kind of intrinsic lying aversion on which the experimental evidence is mixed. In addition, it suggests that the so called "multiple equilibrium problem" may not be that severe.
Keywords: B41; C72; D78; D82; 330; Deception; Implementation; Incentive compatibility; Revelation principle; Social norms and conventions